2011
DOI: 10.1093/ndt/gfr245
|View full text |Cite
|
Sign up to set email alerts
|

Renal involvement in a large cohort of Chinese patients with Castleman disease

Abstract: CD with multicentric type and PC or mixed cellularity variant are often associated with renal complications. Thrombotic microangiopathy-like lesions are the most common pathological characteristics. Chemotherapy can reverse kidney damage in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 15 publications
4
55
0
Order By: Relevance
“…Based on comparable clinical and laboratory chemical findings, some investigators considered that CSP is a variant of multicentric Castleman disease, known as angiofollicular lymph node hyperplasia [4]. Castleman disease is often accompanied by various renal lesions, including amyloidosis, thrombotic microangiopathy, and some forms of glomerulonephritis [5,6]. However, CSP is rarely accompanied by renal lesions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Based on comparable clinical and laboratory chemical findings, some investigators considered that CSP is a variant of multicentric Castleman disease, known as angiofollicular lymph node hyperplasia [4]. Castleman disease is often accompanied by various renal lesions, including amyloidosis, thrombotic microangiopathy, and some forms of glomerulonephritis [5,6]. However, CSP is rarely accompanied by renal lesions [3].…”
Section: Introductionmentioning
confidence: 99%
“…In most previous case reports, the common etiology of renal failure due to CD reported is amyloidosis [13][14][15]. Morita-Hoshino et al reported that autopsy showed the deposition of AA amyloid in multiple organs such as kidney, liver, spleen, and gastrointestinal tract [15].…”
Section: Discussionmentioning
confidence: 99%
“…But in our case, gastric biopsy did not show the deposition of amyloid. Two cohort studies have described renal histopathology in CD patients, reporting thrombotic microangiopathy (TMA)-like lesions as the most common [13,14]. Other than that, CD patients show membranous proliferative glomerulonephritis (MPGN), crescentic glomerulonephritis, or interstitial nephritis [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also reviewed two large cohorts of renal involvement in CD (each had 19 cases). In some cases MPGN-like lesion was included in TMA (13). In other cases, both MPGN-like lesions and TMA were included in small vessel lesions (SVL) (14).…”
Section: Discussionmentioning
confidence: 99%